2012
DOI: 10.1001/archophthalmol.2012.243
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Early Postnatal Weight Gain for Normal Retinal Angiogenesis in Very Preterm Infants

Abstract: Objective To assess WINROP (https://winrop.com), an algorithm using postnatal weight measurements, as a tool for the prediction of retinopathy of prematurity (ROP) in a large geographically and racially diverse study population. Methods WINROP analysis was performed retrospectively on conventionally at-risk infants from 10 neonatal intensive care units.Weight measurements were entered into WINROP, which signals an alarm for an abnormal weight gain rate.Infants were classified into categories of no alarm (unl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 127 publications
(69 citation statements)
references
References 45 publications
(43 reference statements)
2
63
3
Order By: Relevance
“…Accordingly, we found that WINROP was no longer useful for predicting ROP in the later study period. The development of WINROP was originally based on a cohort of very preterm infants at the Queen Silvia Children's Hospital 10 and previously validated in Sweden and other populations in settings with highly developed neonatal care with a sensitivity of 96–100% 7, 8, 15. WINROP only identified half of the infants that needed treatment in the 2015–2016 cohort and this was comparable to outcomes observed in settings with less developed neonatal care and poor oxygen control 9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, we found that WINROP was no longer useful for predicting ROP in the later study period. The development of WINROP was originally based on a cohort of very preterm infants at the Queen Silvia Children's Hospital 10 and previously validated in Sweden and other populations in settings with highly developed neonatal care with a sensitivity of 96–100% 7, 8, 15. WINROP only identified half of the infants that needed treatment in the 2015–2016 cohort and this was comparable to outcomes observed in settings with less developed neonatal care and poor oxygen control 9.…”
Section: Discussionmentioning
confidence: 99%
“…A web‐based prediction tool–weight, insulin‐like growth factor 1, neonatal, retinopathy of prematurity (WINROP) – based on weight development, predicts ROP needing treatment with high sensitivity in settings with highly developed neonatal care 7, 8, but with lower sensitivity in settings with poor oxygen control 9.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the following two cohorts previously assessed by WINROP were utilized: (1) the population-based Extremely Preterm Infants in Sweden Study (EXPRESS) cohort comprising 407 infants born at GA <27 weeks in Sweden during 2004-2007 [17] and (2) a North American cohort comprising 1,706 infants born at GA 22-31 weeks in the USA and Canada during 2006-2009 [14]. In these previous studies the infants were conventionally screened for ROP, according to present screening guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…WINROP has been evaluated in different preterm populations, both in Sweden and worldwide [12,13,14,15,16,17]. Adjustments to the WINROP algorithm have been suggested for specific populations in order to improve its sensitivity and specificity [18].…”
Section: Introductionmentioning
confidence: 99%
“…WINROP was originally developed in a Swedish preterm population and has been validated in another Swedish population with 100% sensitivity and 84.5% specificity [9,12]. In other countries, the sensitivity and specificity of WINROP have been slightly reduced [13,14,15,16,17]. WINROP was previously validated in infants screened for ROP in 2005-2010 at the neonatal intensive care unit (NICU) at the Hospital Civil de Guadalajara, Mexico [16].…”
Section: Introductionmentioning
confidence: 99%